Compensating Activity of the Insurance Guarantee Fund in Poland in 2012–2016 - Urbanek, Joanna (Journal of Finance and Financial Law, 2018)
The Insurance Guarantee Fund plays a unique role on the Polish insurance market. As the only institution in a comprehensive way protects insured and injured. The article discusses the UFG's missions and mode of operation. An analysis of the implementation of the compensatory function in the years 2012–2016 was presented and its interpretation was made. It has been demonstrated that the demand for services provided by UFG is growing.